2020
DOI: 10.1093/jncics/pkaa032
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Nephrotoxicity Associated With Cisplatin-Based Chemotherapy in Testicular Cancer Patients

Abstract: Background Cisplatin-based chemotherapy may induce nephrotoxicity. This study presents a random forest predictive model that identifies testicular cancer patients at risk of nephrotoxicity before treatment. Methods Clinical data and DNA from saliva samples were collected for 433 patients. These were genotyped on Illumina HumanOmniExpressExome-8 v1.2 (964 193 markers). Clinical and genomics-based random forest models generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…14,15 15 (44%) of 34 studies assessed the performance of a single AI model. 13,14,16,17,20,26,[30][31][32]34,36,37,41,42,44 The other studies compared the performance of multiple models with neural networks and tree-based algorithms demonstrating the best performance based on accuracy and AUC-ROC, or other metrics reported in the studies. One study showed similar performance between federated learning (ie, training algorithms using multiple decentralised databases) and centralised approaches for development of AI-based ADE prediction models.…”
Section: Prediction Use Casesmentioning
confidence: 99%
See 4 more Smart Citations
“…14,15 15 (44%) of 34 studies assessed the performance of a single AI model. 13,14,16,17,20,26,[30][31][32]34,36,37,41,42,44 The other studies compared the performance of multiple models with neural networks and tree-based algorithms demonstrating the best performance based on accuracy and AUC-ROC, or other metrics reported in the studies. One study showed similar performance between federated learning (ie, training algorithms using multiple decentralised databases) and centralised approaches for development of AI-based ADE prediction models.…”
Section: Prediction Use Casesmentioning
confidence: 99%
“…13 (19%) of 67 studies included genetic variables to develop prediction models. [41][42][43][44][45][47][48][49][50][74][75][76][77] Most studies including genetic information (nine [69%] of 13) were conducted using secondary research data and compared the performance of multiple AI algorithms. Genetic information was extracted from genetic variant genotyping data and expression profiles.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations